Of vice and men: technological fetishism, unintended consequences and the regulation of human desire - Oleson, James C. (Journal of Theoretical and Philosophical Criminology, 2023)
Most crime science and criminology ontologizes crime, treating it as a self-evident category, existing independently from human observation. Fetishizing scientific method, criminological research often employs crime as a dependent variable against one or more independent variables, reporting statistically significant results. But what constitutes crime (and how, and why) is rarely asked. Even when it is noted, such concerns are typically framed as beyond the scope of scientific criminology. Because most criminology uncritically accepts an ontology of crime, it reproduces existing power asymmetries, facilitating the subordination of marginalized members of society. Technological interventions in criminology tend to assume a natural, even inevitable, rate of crime, and frequently depend upon the persistence of the very crimes they hope to eradicate. But crime is dynamic. It innovates and adapts. Efforts to regulate criminal behavior can produce unintended consequences, driving conduct underground, creating profit motives and illegal markets, and leading to more virulent forms of crime. These outcomes can be easily discerned in vice crime. We survey the history of gambling laws, the prohibition of alcohol and drugs, and the legislative responses to prostitution. Although it would be possible to manage human vices through regulation, socialization, or education, or even to recognize that structural social arrangements create the conditions under which vice becomes irresistible, it is easier—and useful to reinforce existing power arrangements—to frame vice as an individual failing.